In Vitro Degradation Behavior of Ternary Mg-Zn-Se and Mg-Zn-Cu Alloys as Biomaterials - Persaud-Sharma, Dharam (2013)
In this study, the corrosion behavior of Mg-Zn-Se and Mg-Zn-Cu alloys was investigated to evaluate their corrosion behavior related to use as implantable biomaterials. The corrosion behavior of these alloys and a commercially available Mg-Zn alloy were examined using static solution electrochemical testing, dynamic solution gravimetric testing, ion leaching testing, and microscopic evaluation. Fluctuations in the pH of the Dulbecco’s Modified Eagles Medium (DMEM) used for the gravimetric and ion leaching immersion testing were also recorded over the 30-day duration to assess whether the media conditions induced by the alloy degradation would permit for cellular survival. Weight loss experimentation and electrochemical tests revealed the Mg-Zn-Cu alloy to have the greatest corrosion rate.